The modern spaza: how can e-commerce support spaza shops in achieving the six dimensions of food security in a low-income area? - Konz, Jade Carey (Department of Environmental and Geographical Science, 2025)
South Africa (SA) is facing a food insecurity crisis, with those in low-income areas severely affected by multiple forms of malnutrition. Low-income communities rely on neighbourhood spaza shops to meet their shopping needs, yet they are also sources of obesogenic, highly processed foods. The emergence of e-commerce as a new component of the food system, driven by increased internet and smartphone access in low-income communities, presents an opportunity to explore its potential impact on food security. This research therefore examines how e-commerce can support spaza shops in achieving the six dimensions of food security. A case study was undertaken in Mitchells Plain with a spaza shop e-commerce provider – ‘The Company'. Interviews were conducted with nine foreign owned spaza shops, two employees of The Company on multiple occasions, and field notes were taken to evaluate the role of spaza shops in both supporting and undermining food security. The findings indicate that despite retailing high levels of processed foods, spaza shops contribute in varying degrees to all the food security dimensions, but the current impact of e-commerce in this sphere is minimal. The research highlights challenges faced by The Company, such as high levels of competition in the wholesaler market, limited access to economies of scale, as well as the significance of competitive pricing and product range availability on spaza shops' purchasing decisions. Serving the foreign spaza sector presents additional challenges related to the digital divide, language barriers, and the nature of informality. The thesis finds that The Company supports the spaza shop industry however it does not directly improve the spaza's ability to meet the existing six dimensions of food security. Further investigation is required to evaluate the potential benefits of e-commerce for South African owned spaza shops.